HEMPASAN BADAI KAPITALIS - Farid Th. Musa (Jurnal Inovasi, 2008)
Development of Agriculture using modern technology and names pengentasan poorness is not one steps to increase farmer life level. Exactly happened is capitalization in agriculture area exploiting human resource and sumberdaya the nature in rural. The role of government expected as public or community protector exactly not happened, but has become komprador capitalist. Seed usage, fertilizer, company product pesticide, be image of capitalization in agricultural sector which capital intensive, and exactly kills efficiency of farmer to process the agricultural land based on knowledge owned by it. Thereby third usage of equipment produce of above mentioned is striving government to make way for capitalist circle to do newfangled colonization. So this thing is not solution for pengentasan poorness of farmer in rural, but is an action of murder to local wisdom owned by farmer embracing principle subsistensi